Personality disorder comorbidity among substance dependents and its relationship with other axis i disorders and childhood abuse and neglect history - Kural, Sevil; Evren, Cüneyt; Çakmak, Duran (Journal of Dependence, 2005)
Objective: Aim of this study was to evaluate the personality disorder (PD) among substance dependents, to find the differences between alcohol and drug dependents in terms of PD diagnosis and to examine the relationship of PD diagnosis with sociodemographic characteristics, axis I disorders and childhood abuse and neglect history in substance dependents.Method: The study was conducted in AMATEM (Alcohol and Drug Research, Treatment and Training Center) between April 2002 and March 2003. Study sample consisted of 132 male substance dependent (66 alcohol and 66 drug) patients according to DSM-IV criteria, at the end of their detoxification process. Semistructured socio-demographic form, all the modules of Structured Clinical Interview for DSM-IV (SCID-I), SCID-II, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI) and Childhood Abuse and Neglect Questionnaire were applied.Results: The ratio of PD was 34.8%, in substance dependents while it was 22.7% for personality traits. Among substance dependents included in the study highest rate was for antisocial PD (23.5%). Rate of PD was higher in drug dependent group compared to alcohol dependent group. There were no significant differences between groups in terms of current age, marital, educational and employment status. Suicide attempt history, selfdestructive behavior, lifetime major depression and post traumatic stress disorder were higher in those with PD than those without PD. There were no significant differences between groups in terms of other axis I disorders. Rates of physical, emotional abuse and neglect were also higher in those with PD. The mean scores of BDI and BAI were higher in those with PD and personality traits than those who did not have PD. Taking PD as dependent variable in lojistic regression model, history of suicide attempt, emotional abuse and lifetime major depression were found as determinants.Conclusion: It is important to take all spectrum of PD into consideration while planning treatment of substance dependency rather than only making diagnosis of PD. Comorbid PD among male substance dependents was associated with high depression and anxiety symptoms, suicide attempt history, self destructive behavior and childhood abuse and neglect history.
Keywords: Alcohol dependency; personality disorder; depression; anxiety; axis I; childhood abuse